Does Commuting Affect Health? - Annemarie Künn-Nelen (Institute for the Study of Labor (IZA), 2015)
This paper analyzes the relation between commuting time and health in the United Kingdom. I focus on four different types of health outcomes: subjective health measures, objective health measures, health behavior, and health care utilization. Fixed effect models are estimated with British Household Panel Survey data. I find that whereas objective health and health behavior are barely affected by commuting time, subjective health measures are clearly lower for people who commute longer. A longer commuting time is, moreover, related to more visits to the general practitioner. Effects turn out to be more pronounced for women and for commuters driving a car. For women, commuting time is also negatively related to regular exercise and positively to calling in sick.
Keywords: I12; R41; 330; health; commuting time; transportation mode